2002
DOI: 10.1002/path.1221
|View full text |Cite
|
Sign up to set email alerts
|

The proliferation marker pKi‐67 organizes the nucleolus during the cell cycle depending on Ran and cyclin B

Abstract: The proliferation marker pKi-67 ('Ki-67 antigen') is commonly used in clinical and research pathology to detect proliferating cells, as it is only expressed during cell-cycle progression. Despite the fact that this antigen has been known for nearly two decades, there is still no adequate understanding of its function. This study has therefore identified proteins that interact with pKi-67, using a yeast two-hybrid system. A mammalian two-hybrid system and immunoprecipitation studies were used to verify these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
9

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 52 publications
3
33
0
9
Order By: Relevance
“…3B, arrow 7). Furthermore, immunohistochemistry demonstrated upregulation of the proliferation marker pKi-67 22 (data not shown).…”
Section: Quantification Of Apap-induced Liver Necrosis Inmentioning
confidence: 87%
“…3B, arrow 7). Furthermore, immunohistochemistry demonstrated upregulation of the proliferation marker pKi-67 22 (data not shown).…”
Section: Quantification Of Apap-induced Liver Necrosis Inmentioning
confidence: 87%
“…A recent study showed that Ki-67 played a role in the disintegration and reformation of nucleolus, and thereby in entry into and exit from the Mphase of the cell cycle depending on cyclin B1 expression. 38 Either loss of Rb or p16, or overexpression of cyclin D1 correlated with an increased proliferation fraction in some tumors, 17,33 while no such correlation was seen in others. 39,40 Significantly higher Ki-67 LI was observed in Rb-negative than in Rbpositive tumors within the overall tumors in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 antigen is present during G 1, S, G2, and M phases, but not in G0 (11). The Ki-67 antigen may play a role in nucleolus organization during the cell cycle (22) and is necessary for nuclear proliferation (8). Cardiac myocytes were dried on Superfrost Plus slides and postfixed in cold acetone for 30 min.…”
Section: Myocyte Analysismentioning
confidence: 99%